Oncocytic Carcinoma with Liver Metastasis: Unusual Treatment Strategies and Clinical Insights—A Case Report and Review of the Literature - Mohammad Hourani; Selvaraj Giridharan; Fathi Azribi; Hidayath Ansari; Jawaher Ansari (Case Reports in Oncological Medicine)
We report a distinctive case of malignant oncocytic carcinoma originating in the pancreas, an organ rarely associated with such tumours. We discuss the diagnostic journey, highlighting the tumour’s resemblance to renal cell carcinoma but without renal involvement. A significant aspect of this case is the successful and sustained response to combined immunotherapy and tyrosine kinase inhibitors, demonstrating a potential therapeutic pathway for similar rare cases. This study contributes to a deeper understanding of pancreatic oncocytic tumours and their management.